Advanced strategy for energy management and voltage stability in microgrid-a review - Aswathi Ravindran; B. Rubini (Institute of Advanced Engineering and Science, 2026)
Microgrids (MGs) have emerged as transformative solution for improving energy resilience, stability, and sustainability in modern power systems. By incorporating distributed energy resources (DERs), renewable energy sources (RES), and energy storage systems (ESS), microgrids can supply reliable and stable power to local loads while also supporting the main grid during disturbances. Despite their potential, the efficient operation of MGs depends heavily on well-designed energy management and control systems (EMCS). A key challenge lies in addressing inherent variability of RES such as solar and wind, which introduces uncertainty in generation, as well as the dynamic and unpredictable nature of consumer loads. These factors make strong, adaptive, and intelligent energy management strategies crucial for ensuring both voltage stability and reliable operation. This paper presents review of advanced strategies developed for energy management and voltage stability in microgrids. It explores state-of-the-art optimization techniques, intelligent control methods, and emerging management frameworks that aim to balance generation, storage, and load demand efficiently. The study critically analyzes current methodologies, highlights their limitations, and identifies crucial research gaps in literature. By synthesizing recent developments, the paper provides insights in to innovative approaches that can enhance system reliability, optimize resource utilization, and ensure stable microgrid operation under uncertain conditions.